Entomological assessment of hessian fabric transfluthrin vapour emanators for protecting against outdoor-biting Aedes aegypti in coastal Tanzania. - Nicodem J Govella; Alphonce Assenga; Amos T Mlwale; Nosrat Mirzai; Eimear Heffernan; Jennie Moriarty; John Wenger; Vincent Corbel; Justin McBeath; Sheila B Ogoma; Gerry F Killeen (PLoS ONE)
Background A low technology emanator device for slowly releasing vapour of the volatile pyrethroid transfluthrin was recently developed in Tanzania that provides robust protection against night biting Anopheles and Culex vectors of malaria and filariasis for several months. Here these same emanator devices were assessed in Dar es Salaam city, as a means of protection against outdoor-biting Aedes (Stegomia) aegypti, the most important vector of human arboviruses worldwide, in parallel with similar studies in Haiti and Brazil. Methods A series of entomological experiments were conducted under field and semi-field conditions, to evaluate whether transfluthrin emanators protect against wild Ae. aegypti, and also compare the transfluthrin responsiveness of Ae. aegypti originating from wild-caught eggs to established pyrethroid-susceptible Ae. aegypti and Anopheles gambiae colonies. Preliminary measurements of transfluthrin vapour concentration in air samples collected near treated emanators were conducted by gas chromatography-mass spectrometry. Results Two full field experiments with four different emanator designs and three different transfluthrin formulations consistently indicated negligible reduction of human landing rates by wild Ae. aegypti. Under semi-field conditions in large cages, 50 to 60% reductions of landing rates were observed, regardless of which transfluthrin dose, capture method, emanator placement position, or source of mosquitoes (mildly pyrethroid resistant wild caught Ae. aegypti or pyrethroid-susceptible colonies of Ae. aegypti and An. gambiae) was used. Air samples collected immediately downwind from an emanator treated with the highest transfluthrin dose (15g), contained 12 to 19 μg/m3 transfluthrin vapour. Conclusions It appears unlikely that the moderate levels of pyrethroid resistance observed in wild Ae. aegypti can explain the modest-to-undetectable levels of protection exhibited. While potential inhalation exposure could be of concern for the highest (15g) dose evaluated, 3g of transfluthrin appears sufficient to achieve the modest levels of protection that were demonstrated entomologically. While the generally low levels of protection against Aedes reported here from Tanzania, and from similar entomological studies in Haiti and Brazil, are discouraging, complementary social science studies in Haiti and Brazil suggest end-users perceive valuable levels of protection against mosquitoes. It therefore remains unclear whether transfluthrin emanators have potential for protecting against Aedes vectors of important human arboviruses.